Anti-counterfeiting application of a time-differential composite film

By preparing time differential composite films, the mixing of composite glass ceramic powder and cured resins is solved, and the problem of existing anti-counterfeiting materials are easily imitated is achieved, dynamic multi-mode anti-counterfeiting and self-recovery performance is achieved, and the needs of multi-mode dynamic anti-counterfeiting are met.

CN116376288BActive Publication Date: 2025-04-15SHANGHAI INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310353384.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-04-15
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

Existing anti-counterfeiting materials have problems such as being easily counterfeit, being harmful to the human body or having a small range of use, and it is difficult to meet the needs of multi-mode dynamic anti-counterfeiting.

Method used

A time-differential composite film is used to mix the composite glass ceramic powders ZBr and ZI with the cured resin to prepare a film with structural stability and high mechanical strength, and dynamic multimode anti-counterfeiting is achieved by using the difference in afterglow attenuation time.

Benefits of technology

It realizes a dynamic multi-mode anti-counterfeiting and difficult to imitate anti-counterfeiting mode, and has good self-recovery performance and commercial practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116376288B_ABST
    Figure CN116376288B_ABST
Patent Text Reader

Abstract

The invention relates to an anti-counterfeiting application of a time-difference composite film, and aims to propose and prepare a time-dimensional dynamic optical anti-counterfeiting material based on afterglow luminescence time difference; the time-difference composite film is prepared by compounding two composite glass ceramic powders ZBr and ZI with a curing resin, respectively; the film has stable performance, a simple preparation method and low cost; different from traditional anti-counterfeiting materials, the time-difference composite film proposed by the invention is compounded by two materials with different afterglow luminescence times, and after the time dimension is introduced, the anti-counterfeiting means is introduced from single-mode and two-dimensional to three-dimensional dynamic anti-counterfeiting, and the difference of afterglow time is used to realize multi-dimensional dynamic information encryption and reading, and the self-recovery is good, which has great advantages in anti-counterfeiting strength and practicality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of luminescent materials, and in particular to an anti-counterfeiting application of a time-differential composite film. Background Art

[0002] In the information age, privacy and security have always been crucial security issues. The use of luminescent materials as anti-counterfeiting devices has unique advantages. Compared with traditional anti-counterfeiting, its visual identifiability is more convenient, and therefore it has received more and more attention. The static anti-counterfeiting mode of traditional anti-counterfeiting materials can no longer meet actual needs and still faces the risk of being easily counterfeited. Multi-excitation multi-mode luminescent materials can achieve dynamic luminescence. By regulating different traps and intrinsic emission centers in the material to construct different optical properties, different optical anti-counterfeiting forms have become a research hotspot. At present, most anti-counterfeiting materials use fluorescent inks or 3D plastic surface laser anti-counterfeiting. These anti-counterfeiting methods are harmful to the human body or have a small scope of use. Therefore, it is urgent to develop a multi-mode dynamic anti-counterfeiting technology with a wide range of use, good anti-counterfeiting effect, and advanced anti-counterfeiting methods. Summary of the invention

[0003] To solve the above problems, the time-difference composite film provided by the present invention has a stable structure, is not easy to imitate, and introduces a time dimension to achieve dynamic multi-mode anti-counterfeiting. Due to the difference in afterglow decay time of the two composite materials, the time difference of afterglow light is used to achieve the anti-counterfeiting purpose, and has strong recovery performance.

[0004] The present application proposes an anti-counterfeiting application of a time-difference composite film, which is characterized in that: the time-difference composite film is respectively composited by two composite glass ceramic powders ZBr and ZI and a curing resin; and comprises the following steps:

[0005] S1: A method for preparing a composite glass ceramic powder ZBr, comprising the following steps: 2 CO 3 , B 2 O 3 、SiO 2 The raw materials of ZnS and XBr are accurately mixed, melted at high temperature, cooled, and ground into powder to obtain the composite glass ceramic powder ZBr;

[0006] S2: A method for preparing a composite glass ceramic powder ZI, comprising the following steps: 2 CO 3 , B 2 O 3 、SiO 2 , ZnS, and YI raw materials are mixed, melted at high temperature, and ground into powder to obtain the composite glass ceramic powder ZI;

[0007] S3: A method for preparing a time-difference composite film, comprising the following steps: respectively mixing the composite glass-ceramic powders ZBr and ZI with curing resins to form composite glass-ceramic slurries ZBr and ZI, taking out the slurries and curing them to obtain the time-difference composite film.

[0008] Preferably, in step S1, Na 2 CO 3 , B 2 O 3 、SiO 2 The molar amounts of ZnS and XBr are 10mol% to 20mol%, 30mol% to 50mol%, 20mol%-40mol%, 2mol% to 15mol%, and 2mol% to 15mol% respectively; X is one or more of Li, K, and Na; the high-temperature melting temperature is 1000°C to 1250°C; the high-temperature melting time is 5min to 30min; the cooling time is 1h to 2h; and the particle size of the powder after grinding is 1 to 50μm.

[0009] Preferably, in step S2, Na 2 CO 3 , B 2 O 3 、SiO 2 The molar amounts of ZnS and YI are 10mol% to 20mol%, 30mol% to 50mol%, 20mol%-40mol%, 2mol% to 15mol%, and 2mol% to 15mol% respectively; Y is one or more of Li, K, and Na; the high-temperature melting temperature is 900°C to 1200°C; the high-temperature melting time is 5 to 15min; the cooling time is 1h to 2h; and the particle size of the powder is 1 to 50μm.

[0010] Preferably, the step S3 is specifically as follows: after weighing and proportioning the composite glass-ceramic powders ZBr and ZI with the curing resin respectively, adding an appropriate amount of curing agent, stirring until uniform, placing in a centrifuge to centrifuge to remove bubbles and further mixing into uniform composite glass-ceramic slurry ZBr and ZI, pouring the obtained slurry into a mold and curing at a certain temperature to obtain the time-difference composite films ZBr and ZI.

[0011] More preferably, the mass ratio of the composite glass-ceramic powder ZBr and ZI to the curing resin is 1:0.3-3, the viscosity of the slurry reaches 200mPa·s-350mPa·s, the mass ratio of the curing agent to the curing resin is 0-0.1:1, the centrifugation time is 1min-10min, the curing temperature is 20℃-150℃, the curing time is 5min-720min, and the curing resin is a thermoplastic resin, including but not limited to polydimethylsiloxane, acrylic resin, ABS resin, and polyvinyl chloride resin.

[0012] According to another aspect of the present invention, the time differential composite film is applied to multi-mode dynamic optical anti-counterfeiting; comprising the following steps: screen printing and curing the composite glass-ceramic slurry ZBr as the required encrypted information, and screen printing and curing the composite glass-ceramic slurry ZI as the background of the encrypted information for secondary encryption; or screen printing and curing the composite glass-ceramic slurry ZI as the required encrypted information, and screen printing and curing the composite glass-ceramic slurry ZBr as the background for secondary encryption of the information.

[0013] Preferably, the anti-counterfeiting means of the multi-mode dynamic optical anti-counterfeiting application is: the anti-counterfeiting information is encrypted under sunlight; the anti-counterfeiting information is encrypted when excited by ultraviolet light; after turning off the ultraviolet excitation source, the anti-counterfeiting information can be read within 0s-300s; after 300s, the anti-counterfeiting information is encrypted again.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] (1) The time-differential composite film of the present invention has stable performance, high mechanical strength, and good water and oxygen resistance, meeting the performance requirements of the industry.

[0016] (2) The anti-counterfeiting mode of the time-differential composite film of the present invention is novel. It is not limited to the specific excitation wavelength that traditional fluorescent inks rely on to achieve anti-counterfeiting effects, but introduces the time dimension to achieve three-dimensional time-differential anti-counterfeiting. This anti-counterfeiting mode is difficult to imitate, but the reading and erasure of information are simple.

[0017] (3) Since the time-differential composite film of the present invention has good self-recovery properties, after completing the process of information encryption-secondary encryption-reading-encryption, the process can be cycled again in a short time, and its optical performance will not be affected, so it has strong commercial practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The fluorescence emission spectra of the time-differential composite films prepared in Examples 1 and 2 of the present invention;

[0019] Figure 2This is an appearance diagram of the time-differential composite film prepared in Example 1 of the present invention under fluorescent light irradiation;

[0020] Figure 3 This is an appearance diagram of the time-differential composite film prepared in Example 1 of the present invention under ultraviolet light irradiation;

[0021] Figure 4 This is an appearance diagram of the time-differential composite film prepared in Example 2 of the present invention under fluorescent light irradiation;

[0022] Figure 5 This is an appearance diagram of the time-differential composite film prepared in Example 2 of the present invention under ultraviolet light irradiation;

[0023] Figure 6 This is an appearance diagram of the time-differential composite film obtained in Examples 3 and 4 of the present invention under fluorescent light irradiation;

[0024] Figure 7 The time decay fitting curve of the time difference composite film prepared in Example 1 of the present invention;

[0025] Figure 8 This is an appearance diagram showing the change of afterglow decay over time of the time-differential composite film prepared in Example 1 of the present invention under ultraviolet light.

[0026] Fig. 9 This is a comparison diagram of the appearance of the time-differential composite films prepared in Examples 1 and 2 of the present invention, showing the afterglow decay changing with time under ultraviolet light irradiation.

[0027] Fig.10 This is an anti-counterfeiting application diagram of the composite time-difference composite film prepared in Application Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below through the accompanying drawings and embodiments. However, it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the scope of the present invention.

[0029] Embodiment 1:

[0030] This embodiment provides a ZBr time-difference composite film, which converts analytical pure Na 2 CO 3 , B 2 O 3 、SiO 2 , ZnS, NaBr, according to the matrix glass raw material 10mol% Na 2 CO 3 ,40mol%B 2 O 3 ,30mol%SiO2 , 10mol% ZnS, 10mol% NaBr were accurately weighed and placed in an agate mortar, ground evenly in the agate mortar, placed in a corundum crucible and melted in a muffle furnace at 1100℃ for 10 minutes, and then the glass melt was taken out and quickly cast into a mold preheated at 200℃, kept warm for 1 hour, and then cooled naturally. The prepared composite glass ceramic was ground into powder and 10g was taken out and mixed with 8g polydimethylsiloxane and centrifuged to obtain a slurry, which was poured into a cylindrical mold and cured at 1000℃ for 30 minutes to obtain a ZBr time difference composite film.

[0031] Embodiment 2:

[0032] This embodiment provides a ZI time-difference composite film, which converts analytically pure Na 2 CO 3 , B 2 O 3 、SiO 2 , ZnS, KI, according to the matrix glass raw material 10mol% Na 2 CO 3 ,35mol%B 2 O 3 ,35mol%SiO 2 , 15mol% ZnS, 5mol% KI are accurately weighed and placed in an agate mortar. After being ground evenly in the agate mortar, they are placed in a corundum crucible and placed in a box furnace at 1050°C to melt for 10 minutes. Then, the glass melt is taken out and quickly cast into a mold with a preheating temperature of 250°C for forming. The mold is kept warm for 1.5 hours and then cooled naturally. The prepared composite glass-ceramic is ground into powder and 5g is taken out and mixed with 10g polydimethylsiloxane and 1g curing agent and centrifuged to obtain a slurry. The slurry is poured into a cylindrical mold and cured at room temperature for 360 minutes to obtain a ZI time difference composite film.

[0033] Embodiment three:

[0034] This embodiment provides a ZBr time-difference composite film, which converts analytical pure Na 2 CO 3 , B 2 O 3 、SiO 2 , ZnS, LiBr, according to the matrix glass raw material 10mol% Na 2 CO 3 ,40mol%B 2 O 3 ,30mol%SiO 2, 15mol% ZnS and 5mol% LiBr were accurately weighed and placed in an agate mortar. After being ground evenly in the agate mortar, they were placed in a corundum crucible and melted in a muffle furnace at 1100℃ for 10 minutes. Then, the glass melt was taken out and quickly cast into a mold with a preheating temperature of 300℃ for forming. The mold was kept warm for 2 hours and then cooled naturally. The prepared composite glass-ceramic was ground into powder and 5g was taken out and mixed with 5g polydimethylsiloxane and centrifuged to obtain a slurry. The slurry was poured into a cylindrical mold and cured at 60℃ for 180 minutes to obtain a ZBr time-difference composite film.

[0035] Embodiment 4:

[0036] This embodiment provides a ZI time-difference composite film, which converts analytically pure Na 2 CO 3 , B 2 O 3 、SiO 2 , ZnS, NaI, according to the matrix glass raw material 10mol% Na 2 CO 3 , 50 mol% B 2 O 3 , 20mol%SiO 2 , 5mol% ZnS, 15mol% NaI are accurately weighed and placed in an agate mortar. After being ground evenly in the agate mortar, they are placed in a corundum crucible and melted in a muffle furnace at 1200°C for 8 minutes. Then, the glass melt is taken out and quickly cast into a mold with a preheating temperature of 150°C for forming, kept warm for 2 hours, and then naturally cooled. The prepared composite glass-ceramic is ground into powder and 8g is taken out and mixed with 5g polydimethylsiloxane and 0.5g curing agent and centrifuged to obtain a slurry. The slurry is poured into a cylindrical mold and cured at 60°C for 180 minutes to obtain a ZI time difference composite film.

[0037] Application Example 1:

[0038] Using the two time-difference composite film slurries prepared in Example 1 and Example 2 as the matrix, the slurry prepared in Example 1 is screen-printed into the prepared mold, and then the slurry prepared in Example 2 is screen-printed onto the pattern background printed in Example 1 to achieve secondary encryption. The screen-printed mold is placed in an aging oven at 120°C for curing for 10 minutes, and then taken out. After cooling is completed, the film on the mold automatically detaches from the mold, and this film is the time-difference composite film.

[0039] Figure 1 The fluorescence emission diagram of the ZBr and ZI time-differential composite films prepared in Examples 1 and 2 was measured using a fluorescence spectrometer (FLS920, Edinburgh Instruments, UK). Figure 1 It shows that the prepared anti-counterfeiting films have fluorescence emission dominated by blue light emission, and also have a weaker green light emission peak.

[0040] Figure 2 This is the appearance of the time-difference composite film under fluorescent light obtained in Example 1. The prepared anti-counterfeiting film appears milky white under sunlight and still has good flexibility after being folded in half, indicating that the application range of the anti-counterfeiting film is not limited to flat surfaces and has good mechanical properties.

[0041] Figure 3 This is the appearance of the time-differential composite film obtained in Example 1 under ultraviolet light. Figure 1 Corresponding to the fluorescence test results, under 365nm excitation, the sample still exhibits cyan-blue emission and uniform light emission even when folded.

[0042] Figure 4 This is a picture of the appearance of the time-difference composite film prepared in Example 2 under fluorescent light. The prepared anti-counterfeiting film appears the same milky white as Example 1 under sunlight, which shows that the two materials cannot be directly identified from the appearance, and the time-difference composite film prepared in Example 2 still has good flexibility.

[0043] Figure 5 This is the appearance of the time-difference composite film obtained in Example 2 under ultraviolet light. Figure 1 Correspondingly, the anti-counterfeiting film exhibits cyan-blue luminescence, and its fluorescence emission is Figure 3 The fluorescence emission of the two anti-counterfeiting films is similar, indicating that under ultraviolet light, it is still impossible to distinguish the difference between the two anti-counterfeiting films.

[0044] Figure 6 This is the appearance picture of the time-difference composite film prepared in Examples 3 and 4 under fluorescent light. The prepared anti-counterfeiting film appears milky white under sunlight and has a smooth surface. Even if the ratio of some raw materials is changed, a good anti-counterfeiting film can still be prepared, indicating that the preparation of this film is suitable for large-scale industrial production.

[0045] Figure 7 This is the time decay fitting diagram of the ZBr time-difference composite film prepared in Example 1. For the blue light and green light emission peaks of the prepared film, the decay times of the two peaks were monitored respectively. After fitting, the fluorescence decay time at 447nm was 2.10ms, and the fluorescence decay time at 510nm was 2.68ms. The millisecond-level decay indicates that the prepared film is a long afterglow material. The difference in fluorescence decay time at 447nm and 510nm indicates that it corresponds to two different luminescence centers or defects.

[0046] Figure 8This is the appearance of the time-differential composite film prepared in Example 1, when the afterglow decays under ultraviolet light. As time changes, the anti-counterfeiting film is different from the luminescence when the ultraviolet light is continuously excited. The afterglow luminescence shows the characteristics of green emission, which is consistent with Figure 7 Corresponding to the time decay fitting, the afterglow luminescence only presents green light, indicating that there is energy transfer from the blue light emission center to the green light emission center. This energy transfer causes the carriers in the defect center corresponding to the blue light emission to move to the green light emission center after turning off the excitation source, thereby making the afterglow luminescence green.

[0047] Fig. 9 The following is an appearance diagram of the afterglow decay of the time-differential composite films prepared in Examples 1 and 2 under ultraviolet light. It can be seen that as time changes, the two anti-counterfeiting films are different from the luminescence when continuously excited. The afterglow luminescence of Example 1 lasts longer, while the afterglow luminescence of Example 2 is the same as that of Example 1, both are afterglow green light emission, but the afterglow duration is shorter, so there is a difference in afterglow duration between the two.

[0048] Fig.10 The anti-counterfeiting actual application diagram of the time-difference composite film prepared in Application Example 1. When excited by ultraviolet light, the anti-counterfeiting film emits blue light. At the moment when the excitation source is turned off, the anti-counterfeiting film emits green light. At this time, the required encrypted information cannot be read; after 5 seconds, the anti-counterfeiting film gradually shows a green two-dimensional code pattern, which is printed by the time-difference composite film slurry prepared in Example 1; and a light green background appears around the two-dimensional code, which is printed by the time-difference composite film slurry prepared in Example 2; as time changes, at 40 seconds, the afterglow luminescence of the time-difference composite film prepared in Example 2 completely decays, and after 1 minute, the afterglow luminescence of the time-difference composite film prepared in Example 1 completely decays, and the appearance of the entire anti-counterfeiting film is grayish white. At this point, a complete encryption-secondary encryption-reading-self-recovery process ends, and the whole process lasts for 1 minute, indicating that the prepared anti-counterfeiting film can continuously complete encryption-reading-self-recovery in a relatively short time. It can be seen that the application provided by the present invention has a strong self-recovery property.

[0049] The above content is a further explanation of the present invention in combination with the preferred technical solution, and the examples described are part of the examples of the present invention, but not all of the examples. For researchers in the technical field to which the present invention belongs, simple deductions and substitutions can be made without departing from the concept, and other examples obtained without creative work are all within the scope of protection of the present invention.

Claims

1. An anti-counterfeiting application of a time-differential composite film, characterized in that: The time difference composite film is respectively formed by compounding two composite glass ceramic powders ZBr and ZI with a curing resin; The following steps are involved: S1: Mix raw materials containing Na2CO3, B2O3, SiO2, ZnS and XBr in precise proportions, melt at high temperature, cool, and grind into powder to obtain composite glass ceramic powder ZBr; wherein X is one or more of Li, K and Na; S2: Mix raw materials containing Na2CO3, B2O3, SiO2, ZnS and YI, melt them at high temperature, grind them into powder, and obtain composite glass ceramic powder ZI; wherein Y is one or more of Li, K and Na; S3: The composite glass-ceramic powders ZBr and ZI are respectively evenly mixed with polydimethylsiloxane or a curing resin to form composite glass-ceramic slurries ZBr and ZI. If the slurries are directly taken out and cured at this time, time-differential composite films ZBr and ZI can be obtained; if at this time, the composite glass-ceramic slurry ZBr is screen-printed and cured as the required encryption information, and then the composite glass-ceramic slurry ZI is screen-printed and cured as the background of the encrypted information for secondary encryption; or the composite glass-ceramic slurry ZI is screen-printed and cured as the required encryption information, and the composite glass-ceramic slurry ZBr is used as the background and screen-printed and cured for secondary encryption of the information, an anti-counterfeiting product of a time-differential composite film can be obtained.

2. The anti-counterfeiting application of a time-differential composite film according to claim 1, characterized in that: In step S1, the molar amounts of Na2CO3, B2O3, SiO2, ZnS and XBr are 10mol% to 20mol%, 30mol% to 50mol%, 20mol%-40mol%, 2mol% to 15mol%, and 2mol% to 15mol% respectively; the high-temperature melting temperature is 1000°C to 1250°C; the high-temperature melting time is 5min to 30min; the cooling time is 1h to 2h; and the particle size of the powder is 1μm to 50μm.

3. The anti-counterfeiting application of a time-differential composite film according to claim 1, characterized in that: In step S2, the molar amounts of Na2CO3, B2O3, SiO2, ZnS and YI are 10mol% to 20mol%, 30mol% to 50mol%, 20mol%-40mol%, 2mol% to 15mol%, and 2mol% to 15mol% respectively; the high-temperature melting temperature is 900°C to 1200°C; the high-temperature melting time is 5 to 15min; the cooling time is 1h to 2h; and the particle size of the powder after grinding is 1 to 50μm.

4. The anti-counterfeiting application of a time-differential composite film according to claim 1, characterized in that: The step S3 is specifically as follows: after weighing and proportioning the composite glass ceramic powders ZBr and ZI with polydimethylsiloxane or curing resin respectively, adding an appropriate amount of curing agent, stirring until uniform, placing in a centrifuge to centrifuge to remove bubbles and further mixing into uniform composite glass ceramic slurry ZBr and ZI, pouring the obtained slurry into a mold and curing at a certain temperature to obtain the time difference composite films ZBr and ZI.

5. The anti-counterfeiting application of a time-differential composite film according to claim 4, characterized in that: The mass ratio of the composite glass ceramic powder ZBr and ZI to polydimethylsiloxane or curing resin is 1:0.3-3, the viscosity of the slurry reaches 200mPa·s-350mPa·s, when the curing agent is selected to be mixed with polydimethylsiloxane, the mass ratio is 1:10; when the curing agent is selected to be mixed with the curing resin, the mass ratio is 0-0.1:1; the centrifugation time is 1min-10min, the curing temperature is 20℃-150℃, the curing time is 5min-720min, and the curing resin is a thermoplastic resin, including acrylic resin, ABS resin, and polyvinyl chloride resin.

6. The anti-counterfeiting application of a time-differential composite film according to any one of claims 1 to 5, characterized in that: The anti-counterfeiting means of multi-mode dynamic optical anti-counterfeiting application are: under sunlight, the anti-counterfeiting information is encrypted; when excited by ultraviolet light, the anti-counterfeiting information is encrypted; after turning off the ultraviolet excitation source, the anti-counterfeiting information can be read within 0s-300s; after 300s, the anti-counterfeiting information is encrypted again.

Citation Information

Patent Citations

  • Multi-emission multi-process long afterglow fluorescent powder suitable for safety and counterfeiting prevention and preparation method thereof

    CN111088046A

  • Perovskite nanocrystalline glass ceramic membrane laminated composite material

    CN112759267A